Carcinoecium-forming Epizoanthus [Hexacorallia: Zoantharia] and the biology of E. papillosus in the eastern Atlantic, with special reference to the cnidom - Ryland, John S.; Ward, Helen (Zootaxa, 2016)
Epizoanthus is a poorly known zoantharian genus in need of further study. Benthic surveys have shown that E. papillosus (until recently considered rare) is quite abundant in the Celtic Sea, Minches and northern North Sea, occurring as carcin-oecia formed in association with Anapagurus laevis (Anomura, Paguridae) and as smaller free-living colonies. It is also extensively distributed in the western Atlantic. A study of the cnidom in tentacles and mesenteric filaments has shown that carcinoecia contained fewer types and smaller numbers of nematocysts (basitrichs, p-mastigophores, and two different holotrich types) and spirocysts than free-living colonies, probably a consequence of being able to scavenge food from the pagurid. A method for obtaining quantitative estimates of spirocyst abundance is described. The mesenteric filaments of two of the three carcinoecia analysed contained numerous unexploded nematocysts (kleptocnidae) sequestered from the scyphomedusan Cyanea (probably C. capillata), presumably derived from the long tentacles trailing over the sea bed. This occurrence has never previously been recorded. The taxonomic study of larger, deep-sea, carcinoecium-forming species of Epizoanthus is complicated by the same paucity of nematocysts noted for E. papillosus.